The Results of Physical, Radiologic, Pedabarographic, and Quality-of-Life Assessments in Patients with Surgically Treated Intraarticular Calcaneus Fractures - TİMURTAŞ, EREN; POLAT, MİNE GÜLDEN; KURU ÇOLAK, TUĞBA (ELSEVIER SCIENCE INC, 2018)
Calcaneal fractures are complex injuries and have historically had a poor prognosis that results in substantial disability. However, no studies have been performed that analyze both the radiographic and plantar pressure changes after treatment of intraarticular calcaneus fracture. Patients with an intrarticular calcaneus fracture treated at our institution during the study period were identified from computerized hospital records. A total of 36 patients (34 males) completed physical examination and radiographic and dynamic pedobarographic assessments. The follow-up period was from 13 to 82 months (median 38 months). The mean pain score at rest was 3.7 and during activity was 4.0 on a 10-cm visual analogue scale. The mean range of motion of the subtalar joint was restricted. The mean American Orthopaedic Foot and Ankle Society function scale score was 68.1; the mean Short Form-36 physical score was 41.8; and the mental score was 44.9. Pedabarographic results showed that the mean maximum force in the midfoot, forefoot, and toes (p = .001; p = .04; p = .002) and peak pressure in the midfoot, forefoot (p = .001; p = .007), and contact area of the midfoot and toes (p = .038; p = .004) were significantly increased in the injured foot. Radiologic findings showed hindfoot varus, forefoot adductus, and an increase in the medial arch. Even after appropriate anatomic realignment with open reduction and internal fixation of calcaneus fractures, residual differences in plantar pressures and radiographic measures are noted compared to uninjured foot. (C) 2018 by the American College of Foot and Ankle Surgeons. All rights reserved.
Keywords: arthritis; calcaneus; fracture; pedobarography; quality of life; subtalar joint; talus; PRESSURE; PEDOBAROGRAPHY; HINDFOOT